Nocturnal hypertension in high-risk mid-pregnancies predict the development of preeclampsia/eclampsia. Issue 1 (January 2019) - Salazar, Martin R.; Espeche, Walter G.; Leiva Sisnieguez, Carlos E.; Leiva Sisnieguez, Betty C.; Balbín, Eduardo; Stavile, Rodolfo N.; March, Carlos; Olano, Ricardo D.; Soria, Adelaida; Yoma, Osvaldo; Prudente, Marcelo; Torres, Soledad; et al.
Abstract : Objective: The aim of this study was to test if hypertension detected by ambulatory blood pressure monitoring (ABPM) performed at mid-pregnancy, is a useful predictor for preeclampsia/eclampsia (PEEC). Methods: The study was performed in women coursing high-risk mid-pregnancies. Office blood pressure (BP) was estimated as the mean of three values, taken by a specialized nurse after a 15-min interview, and office hypertension defined as at least 140/90 mmHg. Immediately after, an ABPM was started. Diurnal hypertension was defined as ABPM at least 135/85 mmHg during daily activities, nocturnal hypertension as ABPM at least 120/70 mmHg during night rest. The adjusted risk of PEEC was estimated using logistic regression. Results: Eighty-seven women (mean age 31 ± 7 years) with 23 ± 2 weeks of pregnancy were included. The prevalence of office and ABPM hypertension was 13.8 and 40.2%, respectively. The concordance between both hypertension diagnosis was low ( κ = 0.170, P = 0.044). Nocturnal hypertension (35.6%) was more frequent than diurnal hypertension (26.4%). Nocturnal hypertension markedly increased the relative risk of PEEC (OR 5.32, 95% CI 1.48–19.10). The risk of PEEC attributed to diurnal hypertension did not reach statistical significance; and when both, diurnal and nocturnal hypertension were included in the same model, only the second one was a significant predictor ( P = 0.012). The relative risk associated with nocturnal hypertension increased for women not taking acetylsalicylic acid (ASA); (OR 11.40, 95% CI 2.35–55.25). Conclusion: Nocturnal hypertension at high-risk mid-pregnancy is a frequent condition and a strong predictor for PEEC; the risk doubled for women not taking ASA.